Does Managerial Ability Affect Segment Disclosure? Evidence From Indonesia - Atika Atika; Evy Rahman Utami; Alex Johanes Simamora (Journal of Accounting and Investment, 2023)
Research aims: While prior study around segment disclosure has mainly focused on firm characteristics, there is little study on whether managerial characteristics are associated with segment disclosure. This study, therefore, aims to examine the effect of managerial ability on the level of segment disclosure.Design/Methodology/Approach: This study used panel data regression with 556 firm-year observations of Indonesian manufacturing firms during 2017-2020. This study employed the checklist based on PSAK 5 (2015 edition) and adopted a content analysis approach. To measure managerial ability, this study utilized the managerial ability score developed by Demerjian, Lev, McVay (2012) for Indonesian firms. Research findings: The results of this study revealed that managerial ability significantly and positively affected the level of segment disclosure. Higher-ability managers also tended to disclose their segment information more extensively.Theoretical contribution/Originality: This study contributes to the managerial ability literature and the disclosure literature (specifically for segment disclosure). This study is also the first to provide empirical evidence about the effect of managerial ability on the level of segment disclosure.Practitioner/Policy implication: This study results can be used by the Financial Accounting Standards Board of the Institute of Indonesia Chartered Accountants regarding the effectiveness of management approach implementation in Indonesia. Furthermore, the result of this study suggests that managers need to improve their capabilities to accommodate a dynamic business environment.Research limitation/Implication: This study used content analysis to measure segment disclosure, including subjectivity. Nevertheless, this study only investigated manufacturing firms. Further research may expand the industry sample to get a better understanding.